2018
DOI: 10.1063/1.5047471
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional stability of leapfrogging quantum vortex rings

Abstract: It is shown by numerical simulations within a regularized Biot-Savart law that dynamical systems of two or three leapfrogging coaxial quantum vortex rings having a core width ξ and initially placed near a torus of radii R0 and r0, can be three-dimensionally (quasi-)stable in some regions of parameters Λ = ln(R0/ξ) and W = r0/R0. At fixed Λ, stable bands on W are intervals between non-overlapping main parametric resonances for different (integer) azimuthal wave numbers m. The stable intervals are most wide (∆W … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…The rings in this arrangement also exhibit periodic leapfrogging dynamics such that the triangles of the vortex cores rotate around their centers. The axial symmetry is retained for a long time in the leapfrogging dynamics for the triangular configuration, as reported for the vortex-filament model [16,23]. We have numerically confirmed that the axially-symmetric leapfrogging dynamics continue at least until t ≃ 500 for Figs.…”
Section: Gross-pitaevskii Modelsupporting
confidence: 84%
See 2 more Smart Citations
“…The rings in this arrangement also exhibit periodic leapfrogging dynamics such that the triangles of the vortex cores rotate around their centers. The axial symmetry is retained for a long time in the leapfrogging dynamics for the triangular configuration, as reported for the vortex-filament model [16,23]. We have numerically confirmed that the axially-symmetric leapfrogging dynamics continue at least until t ≃ 500 for Figs.…”
Section: Gross-pitaevskii Modelsupporting
confidence: 84%
“…They oscillate and never grow for m = 6. The growth of the m = 6 mode is slow and only affects the long-time dynamics [23]. The time evolution of C m for the rectilinear initial arrangement in Fig.…”
Section: Vortex-filament Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…A focal theme of interest within this nexus of topological charge, nonlinearity and spatial confinement has been the study of vortex rings and simple filaments [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] whose interaction dynamics and even leapfrogging [32][33][34] have been considered. An even more demanding 3D territory that has been less explored (especially so experimentally) has been that of vortex knot structures.…”
Section: Introductionmentioning
confidence: 99%